Late Quaternary palaeoenvironmental change in western Staaten Island (54.5º S, 64º W), Fuegian Archipelago - Ponce, Juan Federico (2011)
Late Glacial – Holocene environmental conditions were interpreted in western Isla de los Estados (Staaten Island) from geomorphological and palynological analysis. The geomorphological data from Caleta Lacroix (54°50′ S; 64 40′ W) indicate the presence of a fossil dune field that suggest exposition of a larger land surface and stronger wind intensity predominantly from SW and W probably during Late Glacial times, when sea level was lower than today. Deglaciation and onset of peat formation in the western coastal area began prior to 12,600 cal BP in response to warmer conditions. The pollen data indicates initial treeless herbaceous and paludal vegetation with scarce Empetrum/Ericaceae type heaths and scrubs as a result of plant invasion and short-term succession vegetal communities spreading over the shoreline areas under locally more humid conditions. The vegetation between 10,300 and 8300 cal BP included dwarf shrub heaths, scrubs, cushion plants and grasses with scattered trees, under warmer and drier climate conditions than today. After 8300 cal BP, more humid conditions allowed the expansion of an open Nothofagus forest associated with dwarf shrub heath communities. It was followed at 6700 cal BP by a gradual closed forest development in association with Drimys winteri and shrub and herb vegetation indicative of Subantarctic Evergreen Forest-Magellanic Moorland vegetation transition under cold and wet conditions. After 5500 cal BP, the rate of evergreen beech forest greatly increased with the development of almost pure Subantarctic Evergreen Forest communities. These vegetation changes accompanied a modification of the climate toward colder and wetter conditions. After 2700 cal BP, the closed forest was replaced by an open Nothofagus forest indicative of warm and dry conditions. The minimum of Nothofagus pollen registered between 1000 and 500 cal BP may correspond to the Medieval Climate Anomaly (MCA) period. All these vegetation changes are in turn related to the positioning and intensity of the Southern Westerlies wind belt, sea-ice Antarctic extent and changes in the sea level.